Peningkatan Minat dan Hasil Belajar Siswa MTs Nurul Falah Kelas IX melalui Model Pembelajaran Jerold E. Kemp Berbasis Multimedia - Raden Roro Kusuma Dwi Nur Ma’rifati; Ahmad Wildan An-Nihhir; Andhika Fatchur Widyanto (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This Classroom Action Research (CAR) aims to improve the interest and cognitive learning outcomes of 9th-grade students at MTs Nurul Falah through the implementation of the Jerold E. Kemp instructional design model integrated with interactive multimedia. The study was initiated due to low student engagement and academic achievement, due to conventional and monotonous lecture methods. The subjects of this research consisted of 25 students. Data were collected using observation sheets, evaluation tests, and student response questionnaires, which were then analyzed descriptively using quantitative and qualitative approaches. The results demonstrated that the application of the multimedia-based Kemp model significantly elevated learning quality across two cycles. Student learning interest in terms of attention surged from 30% in the pre-cycle to 60% in cycle I, reaching 85% in cycle II. This improvement was linearly correlated with cognitive learning outcomes, where the class average score increased from 61.2 (pre-cycle) to 70.8 (cycle I), and reached 82.4 (cycle II). Accumulatively, the classical completeness percentage increased by 52%, rising from 36% in the pre-cycle to 88% at the end of cycle II, thereby successfully exceeding the predetermined success indicator. Furthermore, the questionnaire indicated highly positive student responses with an average score of 4.6 out of 5.0. In conclusion, the integration of the Kemp model and interactive multimedia serves as an efficient and ideal solution to optimize academic performance and learning motivation in Islamic junior high schools. Keywords: Jerold E. Kemp Model, Interactive Multimedia, Learning Interest, Cognitive Outcomes, Madrasah Tsanawiyah